Psychological characteristics of women who choose conscious childlessness - V. V. Kozyreva (Вестник университета, 2022)
The article provides a review of the study of the problem of childlessness in foreign and domestic literature is presented. The results of the author’s research, revealing the psychological characteristics of women, choosing conscious childlessness, are presented. The characteristics of women who consciously choose childlessness for themselves and women with children have been described and analysed by a questionnaire to identify the dominant instinct, the questionnaire “Reproductive Motives”, the California Psychological Questionnaire. Among the psychological traits of childfree women, dominant traits aimed at social and interpersonal relationships, abilities for status, independence and flexibility, achievement through submission and through independence prevail, etc. They are aimed at domination, control of themselves and their lives, receiving material and social benefits from life, moreover, they do not want to bind themselves with responsibility for other people in general, and for children in particular.